(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article describes the need and theoretical aspects of forming students’ value relations in socio-cultural activities based on an axiological approach. The possibilities of developing axiological competence in students, the content of using interactive methods and pedagogical technologies in developing valuable communication skills, are described.